Abraham Lincoln - Kolpas, Norman (Longman Burnt Mill, UK, 1981)
A biography of Abraham Lincoln showing how the backwoods boy became President.
Includes bibliographical references and index.
Keywords: Lincoln, Abraham; Presidents. -- United States -- Biography -- Juvenile literature